The relationship between principal instructional leadership and teacher self-efficacy in student engagement and classroom management: a cross-sectional study in China - Zhang, Naiyuan; Siaw, Yan-Li; Jiang, Na (Frontiers in Psychology, 2025)
IntroductionThis study examines the relationship between principal instructional leadership and teacher self-efficacy in student engagement and classroom management within Chinese primary and secondary schools. Grounded in Bandura’s self-efficacy theory, it addresses two research questions: (1) What is the association between principal instructional leadership and teacher self-efficacy? (2) Which specific leadership dimensions most significantly predict teacher efficacy?MethodsA quantitative research design was employed, with data collected from 459 teachers through two validated online instruments: the Educational Leadership Instrument (ELI) and the Teachers’ Sense of Efficacy Scale (TSES). Data analysis included descriptive statistics, correlation analysis, and multiple regression.ResultsResults demonstrated significant positive correlations between instructional leadership and teacher self-efficacy (r = 0.75–0.84, p < 0.01). Regression analysis identified “work environment support” (β = 0.488) and “teacher-student engagement promotion” (β = 0.518) as the strongest predictive dimensions of teacher efficacy.DiscussionThe findings underscore the pivotal role of instructional leadership in enhancing teachers’ confidence in student engagement and classroom management. This study contributes to leadership literature by highlighting culturally relevant dimensions in non-Western educational contexts, while offering practical implications for principal training programs and professional development initiatives.